Causal factors influencing organizational commitment of employee in the automotive and auto parts industries: A case study of Amata City Industrial Estate Thailand - Rujit, Wilaiwan; Liemsuwan, Tienkaew (Kasetsart Journal of Social Sciences, 2021)
This study analyzed causal factors influencing the organizational commitment of employees in the automotive and auto parts industries of Amata City Industrial Estate Thailand. The research used a structural equation model based on an extensive review of relevant literature. The population and samples were drawn from employees in the automotive and auto parts industries of Amata City Industrial Estate Thailand. A questionnaire survey was used to collect empirical data. The data were analyzed by structural equation modeling (SEM). The results indicated that the model was consistent with the empirical data at a good level (χ2/df = 1.53, RMSEA = .03, p = .00, RMR = .03, GFI = .90, CFI = .97, IFI = .97, TLI = .97). The research findings indicated that the employees showed a high level of organizational climate, job satisfaction, organizational commitment and quality of work life. The results showed that the quality of work life had a direct effect on organizational commitment, and job satisfaction had an indirect effect on organizational commitment through the quality of work life. Moreover, this research found that the organizational climate had an indirect effect on organizational commitment through job satisfaction and the quality of work life. Nevertheless, the combined causal factors in the model could account for 78 percent of the variance of organizational commitment.